The Influence of Brand Image and Product Variation on Consumer Buying Interest of Geprek Bensu (Case Study in Gorontalo City) - Dwiandra Venayla Putri Mulyadi; Andi Yusniar Mendo; Andi Juanna (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine whether brand image and product variety influence consumer purchasing interest at Geprek Bensu restaurants in Gorontalo City. This research method uses a quantitative approach with three variables, namely brand image (X1), product variety (X2), and purchasing interest (Y). The sample used in this study amounted to 96 respondents, who had never made a purchase at Geprek Bensu in Gorontalo City and were the general public of Gorontalo City and students of Gorontalo State University. The sampling technique used was purposive sampling. Data analysis used was descriptive analysis and multiple linear regression analysis. The results showed that brand image had a positive and significant effect on purchasing interest, indicated by a regression coefficient value of 0.551. Product variety also had a positive and significant effect on purchasing interest with a coefficient value of 0.345. Simultaneously, brand image and product variety had a significant effect on consumer purchasing interest. This was indicated by the results of the multiple linear regression test with an F-value of 147.696 and a significance of 0.001. These findings reflect that strengthening brand image and providing product variations that suit consumer preferences can increase purchasing interest, especially among the younger generation.